In vitro selection of the RNA aptamer against the Sialyl Lewis X and its inhibition of the cell adhesion - Jeong, S; Eom, TY; Kim, SJ; Lee, SW; Yu, J (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2001)
Sialyl Lewis X (sLe(X)) is a tetra-saccharide glycoconjugate of membrane proteins. It acts as a ligand for the selectin proteins during cell adhesion of inflammatory process. Aberrant overexpression of sLeX is also a characteristic of various cancer cells, especially for highly malignant ones. In this paper, the sLe(X)-specific RNA aptamer was selected using a random RNA library and its affinity and specificity were measured by Surface Plasmon Resonance technique. Affinity of the selected RNA was increased about 1000-fold as compared with the original RNA pool. RNA aptamer bound more specifically to its cognate sugar than to any other similar sugars. Inhibition of the cell adhesion was also shown by in vitro static assay of sLe(X)-expressing HL60 cells to the E- and P-selectins. It suggests that the high affinity carbohydrate specific RNA aptamer could be used as an alternative to the antibody. (C) 2001 Academic Press.
Keywords: LECTIN-CARBOHYDRATE INTERACTIONS; P-SELECTIN; MONOCLONAL-ANTIBODIES; LIGANDS; RECOGNITION; CARCINOMA; EVOLUTION; LUNG; METASTASIS; EXPRESSION